2021
DOI: 10.3390/ijms22052361
|View full text |Cite
|
Sign up to set email alerts
|

Transient Vasodilation in Mouse 4T1 Tumors after Intragastric and Intravenous Administration of Gold Nanoparticles

Abstract: Gold nanoparticles (AuNPs) are foreseen as a promising tool in nanomedicine, both as drug carriers and radiosensitizers. They have been also proposed as a potential anticancer drug due to the anti-angiogenic effect in tumor tissue. In this work we investigated the effect of citrate-coated AuNPs of nominal diameter 20 nm on the growth and metastatic potential of 4T1 cells originated from a mouse mammary gland tumor inoculated into the mammary fat pad of Balb/ccmdb mice. To evaluate whether AuNPs can prevent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Using the same in vivo model of breast cancer as in the present work, we recently showed that gold nanoparticles transiently increased the volume of blood vessels in tumor tissue after both intragastrical and intravenous administration [ 30 ]. In order to check if a similar effect can be induced by AgNPs, we performed an analysis of the volume of blood vessels in tumor tissue after AgNPs treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same in vivo model of breast cancer as in the present work, we recently showed that gold nanoparticles transiently increased the volume of blood vessels in tumor tissue after both intragastrical and intravenous administration [ 30 ]. In order to check if a similar effect can be induced by AgNPs, we performed an analysis of the volume of blood vessels in tumor tissue after AgNPs treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting aspect analyzed during the present study was the volume of blood vessels in tumor tissue after AgNPs administration. In our recent work using the same experimental model, we showed that gold nanoparticles induce transient vasodilation in tumor tissue after both intragastric and intravenous administration [ 30 ]. In the present study, we did not observe such an effect, which proved that the vasodilating effect was specific to gold nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the recent data showing that 1 mg/kg AuNPs might be around the real therapeutical dose. 25 , 36 , 37 BSA-AuNPs are considered a safe platform among various AuNPs types, nevertheless, their biocompatibility still needs to be carefully assessed. In one of the recent publications, five different doses of AuNPs coated with BSA ranging from 1.16 mg/kg to 5.84 mg/kg were tested for 8 consecutive days after intravenous injections in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The nanomaterial surface may also contain structural defects inducing the formation of reactive groups [36], as well as transition metals that can generate ROS by Fenton and Haber-Weiss type reactions [37]. In addition, environmental oxidants such as ozone, semiquinones, and NO can adsorb to the nanomaterial surface and enter cells through the so-called "Trojan horse effect" [37]. Nanomaterials may also indirectly enable the production of ROS by triggering cellular mechanisms.…”
Section: Mechanisms Of Pro-oxidative and Antioxidant Action Of Nanozymesmentioning
confidence: 99%